2016
DOI: 10.4103/0973-1296.176111
|View full text |Cite
|
Sign up to set email alerts
|

Molecular docking analysis of selected Clinacanthus nutans constituents as xanthine oxidase, nitric oxide synthase, human neutrophil elastase, matrix metalloproteinase 2, matrix metalloproteinase 9 and squalene synthase inhibitors

Abstract: Background:Clinacanthus nutans (Burm. f.) Lindau has gained popularity among Malaysians as a traditional plant for anti-inflammatory activity.Objective:This prompted us to carry out the present study on a selected 11 constituents of C. nutans which are clinacoside A–C, cycloclinacoside A1, shaftoside, vitexin, orientin, isovitexin, isoorientin, lupeol and β-sitosterol.Materials and Methods:Selected 11 constituents of C. nutans were evaluated on the docking behavior of xanthine oxidase (XO), nitric oxide syntha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 18 publications
0
12
3
Order By: Relevance
“…In the present study, 4-hydroxyisoleucine showed interaction with Arg880, Thr1010, and MOS1328 amino acid residues of XO; this was in good agreement with the previous report. [ 9 ] However, phytic acid fails to dock with the XO might due to the general poor binding phenomenon as reported by Akdogan et al . [ 25 ]…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…In the present study, 4-hydroxyisoleucine showed interaction with Arg880, Thr1010, and MOS1328 amino acid residues of XO; this was in good agreement with the previous report. [ 9 ] However, phytic acid fails to dock with the XO might due to the general poor binding phenomenon as reported by Akdogan et al . [ 25 ]…”
Section: Resultsmentioning
confidence: 97%
“…In the present study, 4-hydroxyisoleucine exhibited interaction with Ala165, His201, and Glu202 amino acid residues of MMP-2 and with Ala189 and Gln227 amino acid residues of MMP-9, respectively, this finding was in good agreement with previous reports. [ 9 23 ] However, phytic acid fails to dock with the MMP-2 and -9 might due to the general poor binding phenomenon as reported by Akdogan et al . [ 25 ]…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The molecular docking calculations were performed using the LibDock protocol under the protein-ligand interaction section in Discovery Studio ® 3.1 (Accelrys, San Diego, USA), which the ligand would be structurally rearranged in response to the receptor. Docking was carried out as described elsewhere,[ 23 ] which hinted the target compounds as inhibitors of proteins.…”
Section: Methodsmentioning
confidence: 99%